Effects of Increasing Energy or Lysine in Soybean Meal-Based Diets on Early and Late Finishing Pig Performance - Ty H. Kim; Jamil E. G. Faccin; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,265 finishing pigs (337 × 1050 PIC; initially 110.7 ± 6.14 lb) were used in two 28-d trials to determine the effect of increasing energy or lysine in soybean meal-based diets on early and late finishing pig performance. Pigs were housed in mixed gender pens with 27 pigs per pen and 21 pens per treatment. Soybean meal (SBM) NE values used in diet formulation were either 946 kcal/lb (78% NE of corn; NRC) or 1,212 kcal/lb (100% NE of corn). The treatments were structured as a completely randomized design. Treatments consisted of: 1) a diet containing a high level of SBM which was estimated at 100% NE of corn (High SBM); 2) a diet containing a low level of SBM which was estimated at 100% NE of corn with added feed-grade amino acids (Low SBM); 3) a diet containing a low level of SBM which was estimated at 78% NE of corn with added fat (Low SBM w/fat) to equal the NE in diets 1 and 2; and 4) a diet containing a low level of SBM which was estimated at 100% NE of corn with increased feed-grade AA and increased Lys:NE (Low SBM w/AA). Following the 28-d growth trial in the early finishing phase, pigs were fed a common diet for approximately 30 d. Pens were then randomly allotted to 1 of the same 4 treatments for the late finishing phase (initially 251.5 ± 7.40 lb BW). For both experiments, pigs were weighed and feed disappearance was measured every 14 d to determine ADG, ADFI, F/G, and caloric efficiency (CE). In the early finishing study, there were no differences in ADG (P>0.10), but pigs fed a low level of SBM with increased feed-grade AA and increased Lys:NE (Low SBM w/AA) had increased (P<0.05) ADFI compared to pigs fed a high level of SBM (High SBM). The increased ADFI without increased ADG resulted in poorer F/G (P<0.05) in pigs fed a low level of SBM with increased feed-grade AA and increased Lys:NE (Low SBM w/AA) compared to pigs fed a low level of SBM with added fat (Low SBM w/fat). For CE, pigs fed a low level of SBM with added fat (Low SBM w/fat) had improved (P<0.05) CE compared to pigs fed a low level of SBM with increased feed-grade AA and increased Lys:NE (Low SBM w/AA). In the late finishing study, there was a tendency (P= 0.092) for a treatment effect on F/G where pigs fed the High SBM diet had the best F/G, but there was not a significant difference between any two treatments when using a Tukey multiple comparison adjustment (P>0.05). There was no evidence (P>0.10) for a difference in ADG, ADFI, or CE. Based on the performance of pigs fed the low level of SBM with increased AA and increased Lys:NE (Low SBM w/AA), the lost performance of low SBM diets is not due to a lower Lys:Cal ratio that results when NE is underestimated. Using caloric efficiency, SBM is estimated to contain 94% of the NE of corn based on results of the early finishing study and 125% of the NE of corn based on results of the late finishing study.
Keywords: caloric efficiency; finishing pigs; net energy; soybean meal; swine